Educational Media in Increasing Knowledge and Participation of Prospective Fathers in Preparation for Healthy Pregnancy - Oktalia, Juli; Ichwan, Erika Yulita; Angraini, Diana Hartaty; Widyastuti, Dyah (Poltekkes Kemenkes Jakarta III, 2023)
There have been 85 million pregnancies worldwide are unplanned pregnancies. Of these unwanted pregnancies, 38% ended in abortions, miscarriages, and unplanned deliveries. Efforts to prevent unwanted pregnancies have been attempted in various ways by various parties. At the beginning of 2022, based on media exploration for the Play Store and YouTube applications, we found several applications and videos related to preparing for a healthy pregnancy. Search results from various online media have not specifically focused on the role of men (prospective fathers) in preparing for a healthy pregnancy. With the preparation of healthy pregnancies by men as prospective fathers, it is hoped that the pregnancy occurring can be properly prepared and planned. This study used a quasi-experimental method. The research was conducted at one Community Health Center in the East Jakarta Region. Respondents were prospective grooms (fathers) who met the inclusion and exclusion criteria. The number of respondents was 96 people. The research instrument used was a pre-and post-intervention questionnaire. The treatment given to respondents was providing educational media using video and leaflet media—analysis of research data using univariate analysis, chi-square, and different tests (independent T-test). Two of the respondent's characteristic variables have a significant relationship with the respondent's level of knowledge about healthy pregnancy preparation, namely education level (P value 0.000) and history of information exposure ((P value 0.000). Two of the respondent's characteristic variables have a significant relationship with the respondent's participation in pregnancy preparation healthy, namely the level of income (P value 0.000) and history of information exposure ((P value 0.05). There is a significant difference (<0.000) in the mean level of knowledge and level of participation of respondents in preparation for healthy pregnancies before and after providing education. The group using the media Video-based education has a higher mean participation rate than the group using leaflets (significance <0.05).